The besieged fortress? Urban, highly educated and highly religious: female members of Catholic groups in contemporary Poland - Rejowska, Agata (Culture and religion, 2023)
This paper sheds light on the feelings of exclusion and insecurity among female members of Catholic groups in contemporary Poland. It is based on data gathered in the years 2019–2020 within the research project Resistance and Subordination. Religious Agency of Roman Catholic Women in Poland, which involved 48 in-depth interviews with university-educated Catholic women living in large Polish cities and engaged in various religious groups. The conducted analysis indicates that the interviewees resorted to defensive actions, representing a cultural backlash. Taking into consideration the numerical and institutional dominance of Roman Catholicism in Poland, the overarching question of the paper is: why do the interviewed women feel excluded and at what or at whom is their resentment directed? The analysis draws upon a wider discussion on the ongoing ideological polarisation of contemporary societies, showing the case of a country that is religiously homogenous. The interviewed women recognise some external threats, such as liberal culture and feminism, but also internal ones, namely ritualised, habitual, ‘mainstream’ Catholicism.